PERAN PENGETAHUAN KONSUMEN, KETERLIBATAN KONSUMEN, DAN FAKTOR PSIKOLOGIS KONSUMEN PADA INTENSI BERALIH PELANGGAN DEPARTMENT STORE PURWAKARTA KE BELANJA DARING - Indra Maulana (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
In 2017, retail business has decreased. Moreover, these days, conventional retail businesses such as department store isn’t only competing with similar businesses. Yet, also compete with businesses that use online shopping methods. The rapid of technological advancement and idea of easy access, encourage consumers to have the intention of switching from conventional shopping to online shopping which is considered effective and efficient. This research was conducted to determine the factors that influence the Customer Switching Intention. In this research, three variables that are expected to influence customer switching intention are Consumer Knowledge (X1), Consumer Involvement (X2) and costumer psychological factor (X3). The Data was collected using accidental sampling technique by spreading questionnaires to 100 respondents who are consumers of department store Purwakarta and also had experience of shopping online. Research data is then analyzed through software SPSS 23. From the results of the research, partially, Consumer Knowledge, Consumer Involvement and costumer psychological factor have positive and significant impact on Customer Switching Intention. And all dependent variables simultaneously affect Customer Switching Intention with the value of F count 45,860 and significance level 0,000 < 0,05. And the value of R Square shows the results of 0.589 which means that the whole of the dependent variables simultaneously as much as 58.9%.